Silicon-based ceramic, preparation method and application thereof, and removal method of ceramic core for titanium alloy casting

By using a silicon-based ceramic core prepared with a specific composition and treatment process, and spraying a yttrium oxide coating on the surface, combined with the removal method of alternating soaking of alkali and acid solutions, the poor mechanical properties of the silicon-based ceramic core at high temperatures are solved. The problem of reaction with titanium alloys has achieved efficient mechanical performance improvement and core removal effect.

CN119390459AActive Publication Date: 2025-02-07CENT SOUTH UNIV +1

Patent Information

Application Number
CN202411524559.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The silicon-based ceramic core has poor mechanical properties, large deformation at high temperatures and reacts with titanium alloys, which affects the production pass rate and cost of cast products.

Method used

A silicon-based ceramic consisting of silica, mullite, kaolin and yttrium oxide is prepared by specific mixing, ball milling, pressing, drying and sintering processes, and a yttrium oxide coating is sprayed on the surface. At the same time, a removal method is adopted by alternately soaking alkali and acid solutions with corrosion inhibitors.

Benefits of technology

The high-temperature mechanical properties and porosity of silicon-based ceramics are improved, the chemical reaction inertia with titanium alloy is enhanced, the chemical removal efficiency of the ceramic core is significantly improved, and the problem of core removal is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390459A_ABST
    Figure CN119390459A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-based ceramic, a preparation method and application thereof, and a removal method of a ceramic core for titanium alloy casting, the raw materials of the silicon-based ceramic comprise solid powder and a binder, the solid powder comprises 60-100 wt% of silicon dioxide, 0-10 wt% of mullite, 0-10 wt% of kaolin and 0-20 wt% of yttrium oxide; the mass ratio of the solid powder to the binder is 1: (0.01-0.05); the contents of mullite, kaolin and yttrium oxide are all greater than 0; the silicon-based ceramic provided by the invention has excellent room high temperature mechanical properties and good dissolution performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic cores for titanium alloy casting, and more specifically, to a silicon-based ceramic, a preparation method and application thereof, and a method for removing the silicon-based ceramic core. Background Art

[0002] The hollow blades of aircraft engines and gas turbines are precision parts that are subjected to high temperature and high pressure conditions on the turbine rotor at the rear end of the calcination chamber. They are usually manufactured using alloy melt casting technology. The template material of the hollow part of the hollow blade is called a ceramic core, which is a prefabricated part that needs to be formed and sintered before casting. It needs to be pre-filled into the ceramic shell to provide shape stability and high-temperature mechanical properties during casting. After casting, the ceramic core is removed by chemical methods to form a hollow blade. The dimensional stability and mechanical properties of the ceramic core are key auxiliary materials that determine whether the hollow cavity of the blade can be successfully generated and provide a continuous airflow channel. It is one of the high-end and key products of ceramic products for precision casting.

[0003] At present, the ceramic cores used at home and abroad are mainly aluminum-based ceramic cores and silicon-based ceramic cores. Aluminum-based ceramic cores have better thermal strength and thermal stability, and are structurally stable during sintering and use, have no high and low temperature crystal transformation, and have good high temperature resistance. However, it is difficult to de-core aluminum-based ceramic cores, which inhibits their widespread practical application and development. Compared with aluminum-based ceramic cores, silicon-based ceramic cores have the advantages of low sintering temperature, better controllability of quartz conversion rate, small thermal expansion coefficient, and good de-core performance. However, silicon oxide-based cores also generally have problems such as low high temperature strength, large deformation, and reaction with titanium alloys, which affect the production qualification rate and cost of alloy blades.

[0004] In order to solve the problems of poor high temperature mechanical properties, large deformation and reaction with titanium alloy of silicon-based ceramic core chamber, the present invention provides a silicon-based ceramic core for titanium alloy casting and a preparation and removal method thereof. Summary of the invention

[0005] Based on the above technical problems existing in the prior art, the present invention provides a silicon-based ceramic having excellent room temperature high temperature mechanical properties and good dissolution performance.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] A silicon-based ceramic, wherein the raw materials of the silicon-based ceramic include solid powder and a binder, wherein the solid powder consists of 60-100wt% silicon dioxide, 0-10wt% mullite, 0-10wt% kaolin and 0-20wt% yttrium oxide; the mass ratio of the solid powder to the binder is 1:0.01-0.05; and the contents of the mullite, kaolin and yttrium oxide are all greater than 0.

[0008] In some embodiments, the average particle size of the silicon dioxide is 25-40 μm; the average particle size of the mullite is 10-20 μm; the average particle size of the yttrium oxide is 5-15 μm; and the average particle size of the kaolin is 0.5-2 μm.

[0009] The present invention also provides a method for preparing the silicon-based ceramic according to any of the above embodiments, the method comprising the following steps:

[0010] Silicon dioxide, mullite, kaolin and yttrium oxide powders are mixed evenly to obtain a mixed powder; then a binder aqueous solution is added and mixed evenly; then pressing and molding is performed to obtain a green body; after the green body is dried, it is sintered to obtain a silicon-based ceramic; finally, an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the ceramic core.

[0011] In some embodiments, the sintering temperature is 1250-1450°C.

[0012] In some embodiments, the sintering holding time is 3-6 hours.

[0013] In some embodiments, the binder is polyvinyl alcohol; and the concentration of the binder aqueous solution is 3-10 wt %.

[0014] In some embodiments, the solid-to-liquid ratio of the mixed powder to the binder aqueous solution is 15-20 g:1-3 mL.

[0015] In some embodiments, the method for preparing the silicon-based ceramic comprises the following steps:

[0016] S1, mixing the silicon dioxide, mullite, kaolin and yttrium oxide, and fully drying at a temperature of 100-120° C.;

[0017] S2, ball milling the fully dried raw materials to obtain a mixed powder; wherein the ball-to-material ratio is 2:1;

[0018] S3, adding the binder aqueous solution to the mixed powder, mixing evenly and passing through a 100 mesh sieve; wherein the solid-liquid ratio is 15-20g:1-3mL;

[0019] S4, taking the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0020] S5, fully drying the green body at a temperature of 100-120° C.;

[0021] S6. Place the dried green body in a muffle furnace and sinter it at a temperature of 1250-1450° C. to obtain the silicon-based ceramic.

[0022] The present invention also provides a silicon-based ceramic core, which includes a silicon-based ceramic and a coating on the silicon-based ceramic; the silicon-based ceramic is the silicon-based ceramic of any of the above embodiments or the silicon-based ceramic obtained by the preparation method of any of the above embodiments, and the coating is an yttrium oxide coating.

[0023] In some embodiments, the thickness of the coating is greater than 100 μm; preferably, the thickness of the coating is 150-300 μm; more preferably, 150-250 μm.

[0024] The present invention also provides a method for preparing the silicon-based ceramic core, which comprises the following steps:

[0025] The silicon-based ceramic is prepared by using the method for preparing the silicon-based ceramic in any of the above embodiments, and then an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the silicon-based ceramic core.

[0026] In some embodiments, the spraying method is: spraying the yttrium oxide coating on the surface of the silicon-based ceramic by plasma spraying.

[0027] The present invention also provides a method for removing a silicon-based ceramic core for titanium alloy casting, the method comprising the following steps:

[0028] (1) using the silicon-based ceramic core or the silicon-based ceramic core obtained by the preparation method of the silicon-based ceramic core as a template to cast a titanium alloy to obtain a casting;

[0029] (2) placing the casting with the silicon-based ceramic core in a mixed alkali solution and boiling it, while simultaneously subjecting the casting to ultrasonic treatment;

[0030] (3) After the treatment in the mixed alkali solution is completed, the casting is taken out and soaked in water to remove the residual alkali solution;

[0031] (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing a corrosion inhibitor, reacting at a temperature of 80-100° C., and simultaneously performing ultrasonic treatment;

[0032] (5) Repeat steps (2) to (4) until the ceramic core is completely removed.

[0033] In some embodiments, the mixed alkali solution includes 30-60 wt % potassium hydroxide and 5-15 wt % sodium fluoride.

[0034] In some embodiments, the corrosion inhibitor is at least two of copper salt, molybdate, tungstate, zinc salt, potassium iodate, tropaeolum orange, quaternary ammonium salt, Mannich base, hexadecyltrimethylammonium bromide, sodium lauroyl sarcosinate, and sodium dodecyl sulfate. The composite corrosion inhibitor can effectively inhibit the reaction of hydrochloric acid and titanium alloy under high temperature and high concentration hydrochloric acid solution conditions to avoid damage to the titanium alloy during the core removal process.

[0035] In some embodiments, in step (2), the casting with the silicon-based ceramic core is boiled in the mixed alkali solution for 12-36 hours at a natural atmospheric pressure.

[0036] In some embodiments, in step (4), the concentration of the hydrochloric acid solution is ≤6 mol / L; preferably, 4-6 mol / L.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The silicon-based ceramic of the present invention uses silicon dioxide as a raw material and mullite, kaolin and yttrium oxide as mineralizers, which can promote the sintering of materials and the generation of cristobalite, increase the open porosity of the silicon-based ceramic, improve the collapsibility, and simultaneously form a new phase, which is combined with each other to form a skeleton to enhance the mechanical properties of the silicon-based ceramic. The silicon-based ceramic is used as a ceramic core for titanium alloy casting, and an yttrium oxide coating is coated on its surface, which can effectively improve the chemical reaction inertness between the ceramic core and the titanium alloy.

[0039] The method for preparing silicon-based ceramics provided by the present invention enables the obtained silicon-based ceramics to have excellent room temperature high temperature bending strength, high porosity and good dissolution performance.

[0040] The removal method provided by the present invention adopts alternate immersion of alkali and acid solutions in combination with corrosion inhibitors to allow silicon dioxide and alkali solution, yttrium oxide and hydrochloric acid solution to fully react and disperse, effectively improving the chemical removal efficiency of ceramic cores, and solving the problem of ceramic core removal difficulties that has long plagued the titanium alloy casting field from the source. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the fracture of the silicon-based ceramic prepared in Example 1 of the present invention;

[0042] Figure 2 This is the XRD pattern of the silicon-based ceramic core for titanium alloy casting prepared in Example 2 of the present invention;

[0043] Figure 3 This is a SEM image of the fracture of the silicon-based ceramic core for titanium alloy casting prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0044] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0046] Example 1

[0047] A preparation method of silicon-based ceramics comprises the following steps:

[0048] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 15:2:1:2, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0049] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to form a silicon-based ceramic.

[0050] The SEM image of the silicon-based ceramic fracture obtained in this embodiment is as follows: Figure 1 shown.

[0051] Comparative Example 1

[0052] A preparation method of silicon-based ceramics comprises the following steps:

[0053] Weigh 20g of silica and mullite powder in sequence, ensuring that the mass ratio is 18:2, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3mL of a 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12MPa, and the pressure holding time is 30-60s to obtain a green body;

[0054] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain a silicon base.

[0055] Comparative Example 2

[0056] A preparation method of silicon-based ceramics comprises the following steps:

[0057] Weigh 20g of silica, mullite and kaolin powder in sequence, ensuring that the mass ratio is 17.5:2:0.5, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3mL of a 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12MPa, and the pressure holding time is 30-60s to obtain a green body;

[0058] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain silicon-based ceramics.

[0059] Comparative Example 3

[0060] A preparation method of silicon-based ceramics comprises the following steps:

[0061] Weigh 20g of silica, mullite and kaolin powder in sequence, ensuring that the mass ratio is 17:2:1, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3mL of a 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix evenly and pass through a 100-mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12MPa, and the pressure holding time is 30-60s to obtain a green body;

[0062] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0063] Comparative Example 4

[0064] A preparation method of silicon-based ceramics comprises the following steps:

[0065] Weigh 20g of silica, mullite and kaolin powder in sequence, ensuring that the mass ratio is 16.5:2:1.5, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3mL of a 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12MPa, and the pressure holding time is 30-60s to obtain a green body;

[0066] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain silicon-based ceramics.

[0067] Comparative Example 5

[0068] A preparation method of silicon-based ceramics comprises the following steps:

[0069] Weigh 20g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 16:2:1:1, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3mL of a 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix evenly and pass through a 100-mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12MPa, and the pressure holding time is 30-60s to obtain a green body;

[0070] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain silicon-based ceramics.

[0071] Comparative Example 6

[0072] A preparation method of silicon-based ceramics comprises the following steps:

[0073] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 14:2:1:3, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0074] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0075] Comparative Example 7

[0076] A preparation method of silicon-based ceramics comprises the following steps:

[0077] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 13:2:1:4, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0078] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0079] Example 2

[0080] A preparation method for a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0081] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 15:2:1:2, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0082] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain silicon-based ceramics;

[0083] A 200 μm yttria coating was sprayed on the surface of silicon-based ceramics by plasma spraying to obtain a silicon-based ceramic core for titanium alloy casting.

[0084] The XRD graph and fracture SEM graph of the silicon-based ceramic core for titanium alloy casting obtained in this embodiment are shown as follows: Figure 2 and Figure 3 shown.

[0085] Comparative Example 8

[0086] A preparation method for a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0087] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 15:2:1:2, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0088] The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. for 4-6 hours to obtain silicon-based ceramics;

[0089] A 100 μm yttria coating was sprayed on the surface of silicon-based ceramic by plasma spraying to obtain a silicon-based ceramic core for titanium alloy casting.

[0090] Comparative Example 9

[0091] A preparation method for a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0092] Weigh 20 g of silicon dioxide, mullite, kaolin and yttrium oxide powder in sequence, ensuring that the mass ratio is 15:2:1:2, mix and fully dry in an oven at 120°C; transfer the dried powder into a ball mill for 10-16 hours to obtain a ceramic core powder, with a ball-to-material ratio of 2:1; add 1-3 mL of a 3-10 wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve; weigh a certain mass of the powder under the sieve and place it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0093] The green body is transferred into an oven at 100°C for drying; the dried green body is placed in a muffle furnace to sinter the silicon-based ceramic at 1300°C;

[0094] A 300 μm yttria coating was sprayed on the surface of a ceramic core by plasma spraying to obtain a silicon-based ceramic core for titanium alloy casting.

[0095] Example 3

[0096] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0097] A casting is obtained by simulating titanium alloy casting using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours, the pressure is natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10g / L, 1mmol / L, and 6mol / L, respectively; the casting is taken out and repeatedly soaked in deionized water, and then placed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0098] Comparative Example 10

[0099] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0100] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a 50wt% potassium hydroxide solution and boiled for 8 hours, the pressure is natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10g / L, 1mmol / L, and 6mol / L, respectively; the casting is taken out and repeatedly soaked in deionized water, then taken out and repeatedly soaked in ionized water, and then placed in a 50wt% potassium hydroxide solution and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0101] Comparative Example 11

[0102] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0103] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 30wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours at a natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10g / L, 1mmol / L, and 6mol / L, respectively; the casting is taken out and repeatedly soaked in deionized water, then taken out and repeatedly soaked in ionized water, and then placed in a mixed solution containing 30wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0104] Comparative Example 12

[0105] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0106] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours, the pressure is natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10g / L, 1mmol / L, and 3mol / L, respectively; the casting is taken out and repeatedly soaked in deionized water, and then immersed in a mixed solution of 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0107] Comparative Example 13

[0108] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0109] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours, the pressure is natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10g / L, 1mmol / L, and 8mol / L, respectively; the casting is taken out and repeatedly soaked in deionized water, and then immersed in a mixed solution of 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0110] Comparative Example 14

[0111] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0112] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours, the pressure is natural atmospheric pressure, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water; then the casting is immersed in a 6mol / L hydrochloric acid solution, kept warm at 90°C for 4 hours, and the casting is ultrasonically treated at the same time; the casting is taken out and repeatedly soaked in deionized water, and then immersed in a mixed solution of 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0113] Comparative Example 15

[0114] A method for removing a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0115] A casting is obtained by simulating the pouring of titanium alloy using a silicon-based ceramic core for titanium alloy casting as a template; the casting is immersed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours at a natural atmospheric pressure; the casting is taken out and repeatedly soaked in deionized water; the casting is then immersed in a hydrochloric acid solution containing copper chloride and nasturtium orange and kept warm at 90°C for 4 hours; the concentrations of copper chloride, nasturtium orange and hydrochloric acid are 10g / L, 1mmol / L and 6mol / L respectively; the casting is taken out and repeatedly soaked in deionized water, and then immersed in a mixed solution of 50wt% potassium hydroxide and 10wt% sodium fluoride and boiled for 8 hours; the casting is alternately treated with alkali and acid solutions until the core is completely removed.

[0116] The silicon-based ceramic cores prepared in Examples 1-2 and Comparative Examples 1-9 and the silicon-based ceramic cores for titanium alloy casting were tested for their product expansion rate, open porosity, room temperature strength, high temperature strength, high temperature deflection, and inertness to reaction with titanium alloy. The results are shown in Table 1.

[0117] The silicon-based ceramic core for titanium alloy casting prepared in Example 2 was removed by the removal methods of Example 3 and Comparative Examples 10-15, and the complete removal time of each group was recorded. The results are shown in Table 2:

[0118] Table 1

[0119]

[0120] Table 2

[0121]

[0122]

[0123] As can be seen from Table 1, compared with Example 1, only the composition and content of the mineralizers are changed in Comparative Examples 1-7. Adding three mineralizers simultaneously can significantly improve the room temperature strength, high temperature strength and open porosity of the ceramic core; while compared with Example 2, only the thickness of the coating is changed in Comparative Examples 8-9. When the thickness of the yttrium oxide coating is greater than 100 μm, it can play a good isolation role and prevent the reaction between the silicon-based ceramic core and the titanium alloy.

[0124] As can be seen from Table 2, the ceramic core can be effectively removed by combining alternating high-temperature immersion in alkali and acid solutions with ultrasonic dispersion. Increasing the concentration of potassium hydroxide and adding sodium fluoride can effectively shorten the core removal time. The use of a composite corrosion inhibitor can effectively inhibit the corrosion of titanium alloy by high-concentration hydrochloric acid.

[0125] To sum up, the ceramic core for titanium alloy casting prepared by the scheme of the present invention can not only improve the room temperature strength, high temperature strength and open porosity of the base ceramic core, but also significantly improve the chemical removal rate of the ceramic core, thereby solving the problem of core removal difficulties that has long plagued the ceramic core for titanium alloy casting from the source.

[0126] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0127] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A silicon-based ceramic, characterized in that: The raw materials of the silicon-based ceramic include solid powder and a binder, wherein the solid powder is composed of 60-100wt% silicon dioxide, 0-10wt% mullite, 0-10wt% kaolin and 0-20wt% yttrium oxide; the mass ratio of the solid powder to the binder is 1:0.01-0.05; The contents of mullite, kaolin and yttrium oxide are all greater than 0.

2. The silicon-based ceramic according to claim 1, characterized in that: The average particle size of the silicon dioxide is 25-40 μm; the average particle size of the mullite is 10-20 μm; the average particle size of the yttrium oxide is 5-15 μm; and the average particle size of the kaolin is 0.5-2 μm.

3. The method for preparing the silicon-based ceramic according to claim 1 or 2, characterized in that: The following steps are involved: Silicon dioxide, mullite, kaolin and yttrium oxide powders are mixed evenly to obtain a mixed powder; then a binder aqueous solution is added and mixed evenly; then pressing and molding is performed to obtain a green body; after the green body is dried, it is sintered to obtain a silicon-based ceramic; finally, an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the ceramic core.

4. The method for preparing silicon-based ceramics according to claim 3, characterized in that: The sintering temperature is 1250-1450°C; and / or the sintering holding time is 3-6h.

5. The method for preparing silicon-based ceramics according to claim 3, characterized in that: The binder is polyvinyl alcohol; the concentration of the binder aqueous solution is 3-10wt%.

6. The method for preparing silicon-based ceramics according to claim 3, characterized in that: The solid-to-liquid ratio of the mixed powder to the binder aqueous solution is 15-20 g:1-3 mL.

7. The method for preparing silicon-based ceramics according to claims 3-6, characterized in that: The following steps are involved: S1, mixing the silicon dioxide, mullite, kaolin and yttrium oxide, and fully drying at a temperature of 100-120° C.; S2, ball milling the fully dried raw materials to obtain a mixed powder; wherein the ball-to-material ratio is 2:1; S3, adding the binder aqueous solution to the mixed powder, mixing evenly and passing through a 100 mesh sieve; wherein the solid-liquid ratio is 15-20g:1-3mL; S4, taking the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body; S5, fully drying the green body at a temperature of 100-120° C.; S6. Place the dried green body in a muffle furnace and sinter it at a temperature of 1250-1450° C. to obtain the silicon-based ceramic.

8. A silicon-based ceramic core, characterized in that: It comprises a silicon-based ceramic and a coating on the silicon-based ceramic, wherein the silicon-based ceramic is the silicon-based ceramic according to any one of claims 1-2 or the silicon-based ceramic obtained by the preparation method according to any one of claims 3-7; and the coating is an yttrium oxide coating.

9. The method for preparing the silicon-based ceramic core according to claim 8, characterized in that: The following steps are involved: The silicon-based ceramic is prepared according to the preparation method according to any one of claims 3 to 7, and then an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the silicon-based ceramic core.

10. A method for removing a silicon-based ceramic core for titanium alloy casting, characterized in that: The following steps are involved: (1) using the silicon-based ceramic core according to claim 8 or the silicon-based ceramic core obtained by the preparation method according to claim 9 as a template to cast a titanium alloy to obtain a casting; (2) placing the casting with the silicon-based ceramic core in a mixed alkali solution and boiling it, while simultaneously subjecting the casting to ultrasonic treatment; (3) After the treatment in the mixed alkali solution is completed, the casting is taken out and soaked in water to remove the residual alkali solution; (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing a corrosion inhibitor, reacting at a temperature of 80-100° C., and simultaneously performing ultrasonic treatment; (5) Repeat steps (2) to (4) until the ceramic core is completely removed.

Citation Information

Patent Citations

  • Mass for production of cores and casting moulds

    CA1093276A

  • Silicon-base ceramic core and preparation thereof

    CN101168485A

  • Method for preparing silicon oxide-based ceramic core for titanium and titanium alloy casting

    CN103693976A

  • Raw material for preparing porous ceramic material and preparation method of porous ceramic material

    CN111099913A

  • Additive manufacturing method for ceramic core and shell integrated part

    CN114180945A

Cited By

  • Composite ceramic core for automobile turbine shell casting, preparation method and application

    CN121491275A

  • A composite ceramic core for automobile turbine shell casting, preparation method and application

    CN121491275B